The Agreement of Bank Cooperation with Agent in Providing Branchless Banking with The Realization of Inclusive Finance - Etty Mulyati (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
Expanding access to financial services is essential for all levels of society, considering that many community members still do not know, use, and get banking services and other financial services. Through Branchless Banking, banking products can be reached according to the community's needs to support financial inclusion. In implementing innovative banking practices, the banking industry collaborates with other parties, namely agents supported by information technology facilities. This innovation is carried out electronically and involves third parties outside the bank. In this case, the agent is very vulnerable to risk. The problem is the principle of prudence in the cooperation agreement and the bank's responsibility if the agent in implementing Branchless Banking services harms its customers. The approach method used is the normative juridical approach, which includes research on a positive legal inventory and legal principles and rules governing legal relations. The principle in the prudence of banks regarding cooperation agreements with agents provide Branchless Banking services to support the realization of financial inclusion. Banks are required to implement risk management effectively using information technology, Know Your Customer Principles and Anti Money Laundering, Customer Due Diligence, and in-depth analysis of the assessment of credit applications by debtor customers. The bank is responsible for compensating for the losses if the agent implementing the intelligent behaviour of services harms his customers, considering the agent is acting for and on behalf of the bank. Even though the bank has not made a mistake, the agent is an extension of the bank, 1367 of the Civil Code that a person will also be responsible for people's actions under his/her dependents or objects under his/her supervision.